3D printed shape-memory piezoelectric scaffolds with in-situ self-power properties for bone defect repair - Bing Li; Yichao Ma; Kanwal Fatima; Xiaojun Zhou; Xin Gu; Shuo Chen; Chuanglong He (Journal of Nanobiotechnology)
Abstract Electrical stimulation has been shown to regulate early immunity and late-stage osteogenesis in bone repair. However, achieving in-situ electrical stimulation in the form of self-power in vivo during the initial postoperative stages when the patients have limited mobility remains challenging. In this study, we developed a 3D-printed in-situ self-powered composite scaffold composed of shape memory polyurethane elastomers (SMPU) and polyvinylidene fluoride (PVDF) piezoelectric nanofibers. The composite scaffold demonstrates excellent shape memory performance, allowing for minimally invasive implantation. During the shape memory process, the composite scaffold can provide mechanical force stimulation to PVDF nanofibers to generate charge. Therefore, self-power was achieved through the integration of the shape memory process and piezoelectric effects, and it can be used for in-situ electrical stimulation during the initial postoperative period. Additionally, the composite scaffold can output voltage under continuous mechanical force stimulation, indicating that the patients can apply sustained mechanical force stimulation to the composite scaffold to output voltage through rehabilitation exercises when the patients regain mobility. Both cell experiments and animal studies confirmed that this composite scaffold can effectively regulate the immune microenvironment and enhance osteogenesis. This study successfully achieves in-situ electrical stimulation in the form of self-power by integrating the shape memory process and piezoelectric effects, which is expected to be an effective repair strategy for bone tissue engineering. Graphical Abstract